2018
DOI: 10.1038/s41418-017-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Consensus molecular subtypes of colorectal cancer are recapitulated in in vitro and in vivo models

Abstract: Colorectal cancer (CRC) is a highly heterogeneous disease both from a molecular and clinical perspective. Several distinct molecular entities, such as microsatellite instability (MSI), have been defined that make up biologically distinct subgroups with their own clinical course. Recent data indicated that CRC can be best segregated into four groups called consensus molecular subtypes (CMS1-4), each of which has a unique biology and gene expression pattern. In order to develop improved, subtype-specific therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
171
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(192 citation statements)
references
References 59 publications
10
171
0
Order By: Relevance
“…not attributable to infiltrating immune or stroma cells. In further support of this, paired pCRCs and PDXs showed consistent expression levels; 3 out of 15 primary tumors and their paired xenografts showed highly elevated MIR31HG expression (Supporting Information: Fig. S3).…”
Section: Resultssupporting
confidence: 61%
“…not attributable to infiltrating immune or stroma cells. In further support of this, paired pCRCs and PDXs showed consistent expression levels; 3 out of 15 primary tumors and their paired xenografts showed highly elevated MIR31HG expression (Supporting Information: Fig. S3).…”
Section: Resultssupporting
confidence: 61%
“…However, a recent study revealed that most xenograft models maintain the original subtype. 51 Consistently, the CGH results showed that HCT116 cells exhibited minimal genomic changes upon multiple passages (Fig. S9).…”
Section: Discussionsupporting
confidence: 74%
“…[12,13] These cell lines represent ad iverses et of tumors, spanningt he four subtypes of CRC andb oth MMR-and MMR + phenotypes. [14,15] The toxicities of RhPPO,w hich selectively targets MMR deficiencies,a nd the non-selectiveF DA-approved chemotherapeutic cisplatin, which covalently binds the abundant d(GpG) motifs present in all DNA (Figure 1), were assessed in this cell line panel using al uciferase-based luminescence assay which measures ATPf rom living cells. Dose-responsec urves and corresponding IC50 values (50 %i nhibitory concentration) were determined for each therapeutic and are shown in Figure 2 and Table S2 (Supporting Information).…”
mentioning
confidence: 99%